Ciemne strony zasady wzajemności - Łukaszyński, Janusz (Dark side of the rules of reciprocity, 2007)
The rule of reciprocity is one from general, permanent regulators of social, economic and political life. The rule of reciprocity working as psychological and cultural basis for mechanisms giving reasons for human’s behaviour. The rule of reciprocity relates to the customs moral and to legal norms. The article presents different ways of understanding the dark side of social rules of reciprocity.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (11); 2007; nr 1188, s. 15-24